The Islamic Scaffolding–Based REFLECT Model for Developing Students’ Spiritual Awareness - Andhika, M. Rezki; Ridwan, Yusup; Iskandar, Rusdy; Hafinda, Tengku; Makmur, Makmur; Haryanti, Enny (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study aims to analyze the implementation of Islamic Scaffolding within the REFLECT model (Review, Engage, Focus, Learn, Evaluate, Construct, and Transfer) in fostering students’ reflective and spiritual understanding in Akidah Akhlak learning. The study adopts a qualitative descriptive–interpretative approach using a case study design conducted in the Madrasah Ibtidaiyah Teacher Education (PGMI) Study Program at STAIN Teungku Dirundeng Meulaboh. Data were collected through classroom observations, in-depth interviews with lecturers and students, and analysis of learning documents. The participants consisted of lecturers teaching Akidah Akhlak courses and PGMI students actively engaged in the learning process. Data were analyzed using thematic analysis through processes of data reduction, categorization, interpretation, and meaning construction. The findings indicate that the integration of Islamic Scaffolding within the REFLECT model facilitates a reflective, collaborative, and transformative learning environment, in which lecturers function as spiritual scaffolders guiding students through processes of muhasabah and tazakkur. This study contributes to the enrichment of scaffolding theory by incorporating the dimensions of ta’dib and tazkiyatun nafs, positioning the model as a holistic Islamic learning paradigm oriented toward the development of spiritually aware, reflective, and morally grounded students.